THE CORRELATION STUDY IN STUDENTS TRANSLATION ABILITY AND READING COMPREHENSION FOR THE ELEVENTH GRADE AT MAN 1 BAUBAU - Risda, Risda; Maneba, Sanaria; Nety, Nety (Jurnal Akademik FKIP Unidayan, 2023)
Problem formulation in this research was whether there is correlation between students translation ability and reading comprehension at MAN 1 Baubau students. This research aimed to determine whether the correlation between students translation ability and reading comprehension at MAN 1 Baubau students. This was a quantitative research. The subject of this research were 24 eleventh grade students of MAN 1 Baubau. Data collection in this research used a research instrument in the form of a test distributed to students to determine the correlation between students translation ability and reading comprehension. Data were analyzed using Statistical Product and Service Solution (SPSS) version 22.0. Based on the results of the research and data analysis, it was concluded that there is correation between students translation ability and reading comprehension from the 11th graders of MAN 1 Baubau. This conclution was based on the results of statistical analysis which found a significance level of 0,754 where r table is 0,404. The rxy is greather than the r table value (0,754>0,404) and the significance value is less than (0,5) or other words the Null hypothesis (Ho) is rejected and the Alternative hypothesis (Ha) is accepted.